Spatio-temporal variability of groundwater quality in an irrigated area in the Brazilian semiarid region (Research, Society and Development, 2020)
The objective is to analyze the influence of climatic seasonality on the quality of groundwater in the Irrigated Perimeter of Baixo Acaraú - CE. For this, hydrochemical analyzes of the attributes of HCO3-, Ca2+, Cl-, CE, Mg2+, K+, pH, RAS, Na+, SDT, SO42- were performed in the months of June and November 2015 and 2016. The analysis was carried out of grouping by the SPSS 16.0 software, where the group means were compared by the T test at the level of 5% of significance and presented in the form of a “boxplot”. In the classification of waters, the Piper's Diagram was applied and for irrigation the methodology of the United States Salinity Laboratory, using the QUALIGRAF software. Seasonality did not influence the formation of groups. The formation of 2 groups occurred, where group 2, presented high values of sodium. The high levels of chloride in group 2 are mostly due to the leaching of agricultural fertilizers. The high sodium adsorption ratio (RAS) in group 2, can reduce the rate of soil infiltration. In the water classification, there was a predominance of the sodium-chloride class. For irrigation, a predominance of classes C2S1 and C3S1 was observed.